Parameter Analysis in Urban Planning: A Case Study of Street Culture Development in Surat - Arora, Samiksha; Sengottaiyan, Krishnamoorthy (Journal of Progress in Civil Engineering, 2025)
Urban designing, as we know is an approach through which a city can be developed as productive place for its citizens. We being the sole planners, work for the people and hence, I believe that cities should be planned to develop it in a specific agenda keeping its people at prior. India is a country with diverse religion and cultures. Urban streets play a crucial role in how this growing number of people in our cities circulate about, interact, conduct business, and so forth. Many Indian cities have streets where people of the city socialize and spend time. Therefore, the design of streets is of utmost significance. Aim of this study is to understand the spatial ethnography on Udhana magadalla road in Surat city and analyses the spatial and social forces that triggered the development of a street as a public space in Surat city. The main factors that play a role in this thesis are people and hence primary data collection is considered the base.